The role of MgO nanoparticles on the corrosion resistance of hot-dip Al–Zn coating - Seyed Reza Siasi Rad; Kamran Dehghani (Heliyon)
This study investigates the impact of MgO nanoparticles (0, 0.1, 0.5, and 1 wt%) on the corrosion behavior of hot-dipped galvalume (Zn-55Al-1.6Si) coating. The corrosion behavior of coatings was assessed using a salt spray, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization tests in air-saturated 3.5 wt% NaCl solution. The surface of the coatings was examined using field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM). The results revealed that MgO nanoparticles were mainly located in zinc-rich interdendritic areas and filled the micro-holes within the coating. By creating a protective shield and separating the coating from the corrosive agents, these nanoparticles enhanced the corrosion resistance of coatings. Notably, the galvalume coating with the highest MgO nanoparticle content (1 wt%) exhibited the best corrosion resistance.